FRAMING ANALYSIS USING ROBERT ENTMAN’S MODEL IN NEWS COVERAGE OF SEXUAL VIOLENCE CASES AT THE STATE ISLAMIC UNIVERSITY OF NORTH SUMATRA ON ONLINE MEDIA KOMPAS.COM AND DETIK.COM - Winda Kustiawan; Nursamsiah Pasya Hasibuan; Defi Nurfajaria; Muhammad Syarif Harefah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2025)
This study examines how the online media outlets Kompas.com and Detik.com frame the news coverage of a sexual violence case at the State Islamic University of North Sumatra (UINSU), using Robert Entman’s framing analysis model. In the context of reporting on sensitive issues such as sexual violence, the media do more than convey information they also shape public perception and influence the direction of social discourse. This research employs a descriptive qualitative approach with framing analysis to explore four key elements in media narratives: problem definition, causal interpretation, moral evaluation, and treatment recommendation. The findings reveal that Kompas.com adopts a more humanistic and structural approach, emphasizing the victim’s suffering, the role of patriarchal culture, and the need for educational reform. In contrast, Detik.com takes a more legalistic stance, highlighting legal processes and institutional responses to the perpetrator. These differing approaches reflect distinct editorial perspectives and significantly impact how society perceives and responds to sexual violence on campus. Kompas.com constructs a narrative that fosters collective awareness of the need for systemic change, whereas Detik.com reinforces confidence in legal resolutions. These findings demonstrate the influential role of mass media in determining the focus and values of news coverage. The framing employed by media outlets can shape public opinion, influence policy directions, and affect support for victims. Thus, the media are expected to take greater responsibility in crafting narratives that are fair, balanced, and victim-centered, in order to promote more progressive social transformation within higher education environments.